Analysis of Indonesian Morphological Errors in The Essays of Indonesian Language Learners for Foreign Speakers (BIPA) at Alekawa Language & Culture Center - Syarif, St. Nuraisyah; Hasriani, Hasriani; Sakaria, Sakaria (Universitas Negeri Makassar, 2025)
Abstract. This study aims to describe morphological errors in Indonesian language compositions written by foreign language learners at the Alekawa Language & Culture Center. The morphological errors will be described in this study are errors found in affixation, reduplication, and abbreviation. This study uses a qualitative research design by involving documentation in the form of BIPA students' essays at Alekawa to collect phenomena to be studied and discussed in depth. This study uses data cards to analyze documents in the form of BIPA student essays. The data obtained were analyzed by using corder error analysis technique. The results of this study show that there are 22 morphological errors in the BIPA students' essays, namely there are 21 affixation errors and 1 reduplication error. In this study, no words using abbreviations were found in the writings of A1-level BIPA students because the grammar of abbreviations had not yet been taught to A1-level BIPA students, so BIPA students did not use abbreviations in their writing. The results of this study are expected to provide feedback for BIPA teachers, BIPA institutions, and further researchers. This research is also expected to be a reference material for BIPA teachers to be able to improve the learning of BIPA grammar morphology material at the A1 level. Keywords: BIPA learning, writing skills, morphology, essay, language errors